PRINSIP GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN BADAN USAHA MILIK NEGARA PERSFEKTIF HUKUM BISNIS - Wiraguna, M. Aji; Hidayah, Ardiana (Faculty of Law, University of Palembang, 2024)
The implementation of Good Corporate Governance (GCG) as an effective company management system is the implementation of GCG principles which include Transparency, Accountability, Responsibility, Independence, and Fairness in company management. State-Owned Enterprises (BUMN) as entities owned by the state have a significant role in managing the national economy to achieve community welfare. It is expected that the implementation of GCG principles can be optimized in business activities to gain profits and improve the financial performance of the BUMN itself.